Association between seropositivity to BVD virus, Leptospira interrogans and Neospora caninum and abortions in small holder farms in the dairy belt of Boyacá, Colombia - Moreno Figueredo, Giovanni (2017)
The aim of this study was to determine, through a case-control study, the association between sero-positivity to some infectious agents and the report of reproductive alterations in animals and farms in Boyacá, Colombia. «Case» farms (n=5) were considered those with a frequency of abortions higher than 10% and as «control» farms (n=10) those with abortion frequencies lower than 3%. In each farm, blood samples were collected from 10 heifers, 10 cows from 1st and 2nd calving and 10 cows from >2 calvings. It was used the seroneutralization test for the detection of antibodies against bovine viral diarrhea virus (DVB), the microagglutination test for seven serovars of Leptospira interrogans and the indirect immunofluorescence test for Neospora caninum. The highest seropositivity were for DVB (76.4%, 15/15 farms), serovar Hardjo (23.1%, 14/15 farms) and N. caninum (10.7%, 12/15 farms) and without significant differences between case farms and control farms. The serological result of each animal as a risk factor against the abortion condition was evaluated, finding an Odds Ratio (OR) of 10.11 for DVD and 3.88 for Hardjo. No association was found as a risk factor for abortions for other pathogens.